Activating Continuity in Post-Conflict Environments for African and African American Communities in Toni Morrison’s Paradise and Chimamanda Ngozi Adichie’s Half of a Yellow Sun - Atieh , Majda (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This essay addresses subversive female responses in certain African and African American texts which imagine a decolonial modernity and creatively perceive possibilities for realizing tradition and communal awareness in architecture. In this regard, Paradise, by African American critic and novelist Toni Morrison, envisions a persistent spatial bondage that is reflected in the design of modernity and ultimately suggests an architectural freedom that is realized through narratological activation of effaced historical continuity in the isolative modern design. On the other hand, Half of a Yellow Sun, by Nigerian novelist Chimamanda Ngozi Adichie, presents the architecture of postcolonial modernity as precipitator of the warring African community’s rift that blocks any cultural expression of collective agency. Adichie’s narrative suggests a liberatory osmosis of domestic and educational architectures to disrupt the traumatic ideologies of class and gender and initiate communal healing. So, both Morrison’s and Adichie’s narratives propose a utopian possibility for renovating modern architecture to recognize continuity in culture and community.